Advances in Microalloyed Steels - Uranga, Pello (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In response to the demanding requirements of different sectors, such as construction, transportation, energy, manufacturing, and mining, new generations of microalloyed steels are being developed and brought to market. The addition of microalloying elements, such as niobium, vanadium, titanium, boron, and/or molybdenum, has become a key tool in the steel industry to reach economically-viable grades with increasingly higher mechanical strength, toughness, good formability, and weldable products. The challenges that microalloying steel production faces can be solved with a deeper understanding of the effects that these microalloying additions and combinations of them have during the different steps of the steelmaking process.